The Business Model Canvas – narzędzie zarządzania dla start-upów - Pierścieniak, Marek (Wydawnictwo Uniwersytetu Rzeszowskiego, 2016)
The aim of the article is a presentation of the concept of The Business Model Canvas as a tool that supports the process management in the newly created organization and involvement in scientific discussion on the usefulness of such tools in practice. For this purpose a case study, which allowed to present copyright reflection associated with the use Canvas model for service management "dobrerecezje.pl." The research part of the results of the assessment of the usefulness of this tool from the perspective of owners of start-drop – people starting business operations. Model Canvas in the planning phase assists in the tasks and activities necessary to start operations in the initial phase helps in ensuring all the elements and from the perspective of annual activity helps determine the direction of development.
Keywords: business models; model Canvas; start-up; management tools